Sinyal informasi keuangan dalam konteks kesulitan keuangan - Wonok, Shalomega Giacinta Chiensi; Sardjono, Olivia Y. M. (Riset Akuntansi dan Manajemen Pragmatis, 2025)
This study examines the role of financial information signals in explaining financial distress among property and real estate companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Drawing on signalling theory, this research investigates whether profitability, liquidity, and leverage convey meaningful signals regarding a firm’s financial condition. Financial distress is measured using the revised Altman Z’’-Score and classified into safe, grey, and distress categories. Using a quantitative approach with multinomial logistic regression on 128 firm-year observations, the findings reveal that liquidity and leverage significantly influence financial distress, while profitability does not exhibit a significant effect. These results indicate that solvency and capital structure provide stronger distress signals than accounting profitability in asset-intensive industries. This study contributes to the financial distress literature by highlighting the asymmetric signalling power of financial ratios in the property and real estate sector.